2023
DOI: 10.1186/s13063-023-07111-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of virtual supervised tooth brushing on caries experience and quality of life among primary school children: study protocol for a randomized controlled trial

Abstract: Background Dental caries is one of the most common diseases affecting children world widely as well as in the Kingdom of Saudi Arabia. Supervised tooth brushing programs are implemented throughout the world to provide young children’s developing teeth with additional fluoride as a form of dental caries prevention. While school-based supervised tooth brushing programs have been proven to improve young children’s oral health, virtual supervised teeth brushing programs have not been assessed. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
1
0
3
Order By: Relevance
“…The results of the study confirm the need for educational interventions aimed especially at families with low socioeconomic status. This intervention can be effective in increasing parents’ knowledge and skills to help them recognize their child’s dental needs [ 34 ]. In contrast, a study by Nurit et al found that despite higher education, mothers’ knowledge of their children’s oral health was incomplete [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study confirm the need for educational interventions aimed especially at families with low socioeconomic status. This intervention can be effective in increasing parents’ knowledge and skills to help them recognize their child’s dental needs [ 34 ]. In contrast, a study by Nurit et al found that despite higher education, mothers’ knowledge of their children’s oral health was incomplete [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tindakan preventif meliputi pemberian fluor (Al-Shahrani et al, 2020;Ruff et al, 2022) dan penggunaan pit fissure (Liu et al, 2018;Zhang et al, 2023) sealant telah terbukti efektif dalam mengurangi risiko karies gigi. Di sisi lain, tindakan promotif bisa meliputi kegiatan penyuluhan kesehatan gigi (Husna & Prasko, 2019) dan program sikat gigi massal (Alayadi et al, 2023). Kegiatan-kegiatan ini bertujuan untuk meningkatkan kesadaran dan pengetahuan masyarakat, khususnya anak-anak, mengenai karies gigi dan strategi pencegahannya.…”
Section: Pendahuluanunclassified
“…A saúde bucal dos escolares é objeto de preocupação diante da possibilidade de interferir de maneira significativa na educação e na qualidade de vida, tendo em vista a cárie, doença acometida mais comumente em crianças, que podem ter seu psicológico impactado negativamente (Alayadi et al, 2023).…”
Section: Introductionunclassified